Borrowing by the Fund : Operational Issues. (Policy Papers; Policy Paper, 2009)
An increase in the Fund's resources available to assist its members represents an important part of the multilateral response to the global crisis. To this end, the IMFC agreed in April that there should be an increase in the resources available to the Fund through immediate financing from members of USD 250 billion, subsequently incorporated into an expanded and more flexible New Arrangements to Borrow (NAB), increased by up to USD 500 billion. Recognizing that IMF is, and shall remain, a quota-based institution, the IMFC also called for the completion of the Fourteenth General Review of Quotas by January 2011. This is consistent with borrowing being a temporary arrangement to supplement Fund resources to address the current crisis.